THE ROLE OF IMMIGRATION POLYTECHNIC CADETS IN PREVENTING NON-PROCEDURAL PMI (INDONESIAN MIGRANT WORKER) SOCIALIZATION WITH IMMIGRATION OFFICE CLASS II OF NON-BORDER CONTROL MADIUN IN MAGETAN REGENCY - Ale Alfero Deputra; Respati Triana Putri; sri Kuncoro Bawono (Polteknik Imigrasi, 2021)
Nowadays, in order to meet the increasing economic needs, one of the attractive jobs for Indonesians because of their promising income is working abroad as Indonesian Migrant Workers (PMI). However, due to the lack of understanding and knowledge of the community as well as several other limitations, many of the people who are interested in becoming PMI use channels that are not in accordance with the applicable administration. The presence of Non-Procedural PMI can actually endanger the safety of the person and give a bad image to other countries. Therefore, taking advantage of the Latjapura moment in 2021, the Immigration Polytechnic Cadets took the initiative to take part in socializing the prevention of Non-Procedural PMI together with the Madiun Immigration Office in Magetan Regency. With this socialization method, this activity went smoothly and resulted in an understanding to the public of the dangers of becoming a Non-Procedural PMI and the ease of making passports for PMIs through proper administration.